Efforts to Improve Pencak Silat T-Kick Skills Using the Drill Methods in School Extracurricular Activities - Aisha, Majesta Wahyu; Utamayasa, I Gede Dharma; Kusuma, Angga Indra; Phanpheng, Yanyong; Fufu, Ronald Dwi Ardian (JSES : Journal of Sport and Exercise Science, 2026)
Purpose: This study aimed to improve T-kick skills in Pencak Silat among students at Ta'Miriyah Surabaya High School through the drill method. The T-kick is a fundamental technique requiring precision, coordination, and consistency. The drill method was selected due to its emphasis on repetitive and focused practice, allowing students to refine specific technical components effectively. Materials and Methods: A quantitative experimental design was applied, involving 20 students participating in the Pencak Silat extracurricular program. The training program lasted six weeks, with sessions conducted twice weekly. To measure improvement, students were assessed using a pre-test before the intervention and a post-test after completing the training. Data were analyzed using descriptive statistics and a paired t-test to determine the significance of differences between pre- and post-test results. Result: The findings indicated a significant improvement in students’ T-kick performance following the drill-based training. This enhancement was reflected in better accuracy, speed, and overall execution of the technique. The average pre-test score increased from 30.92 to 34.17 in the post-test. Statistical analysis yielded a p-value of 0.000, confirming a statistically significant difference between the two measurements. Conclusion: The drill method proved effective in enhancing T-kick skills among high school students. The structured and repetitive nature of this approach supports skill acquisition and technical mastery in martial arts training. This study highlights the importance of targeted training methods and provides practical implications for coaches and educators in developing students’ fundamental Pencak Silat techniques at the school level.